API Copyrights Revisited: Deliberating on the main arguments in recent sets of briefs filed in support of Google's U.S. Supreme Court petition. - Samuelson, Pamela (Communications of the ACM, 2019)
The article discusses the American technology company Google's legal briefs in a U.S. Supreme Court petition to review lower courts' judgments in lawsuits concerning application program interfaces (APIs) copyright law. An overview of the U.S. Court of Appeals for the Federal Circuit's (CAFC's) ruling on copyright protection for the use of Java API by Google is provided.